Do reading comprehension assessment tests result in the same reading profile? A study of Spanish primary school children. (20th December 2019) - Calet, Nuria; López‐Reyes, Rocío; Jiménez‐Fernández, Gracia
Abstract : Background: Detecting reading comprehension difficulties is challenging because many factors are involved in comprehension ability. Various reading comprehension tests can be used to detect difficulties but often do not yield the same results. Method: Our aim was to analyse the agreement between three commonly used standardised reading comprehension tests (ECOMPLEC, ACL and PROLEC‐R) in the detection of reading comprehension difficulties in Spanish. A total of 139 children (72 fifth graders and 67 sixth graders) at the same public‐sector school participated in this study. The three reading comprehension tests were administered, together with word and nonword reading, vocabulary and nonverbal intelligence measures. Results: Modest intercorrelations among the tests were found. The consistency of classification for each reading profile across the three reading comprehension tests was low. The results show different reading comprehension profiles depending on the test used. Conclusions: It is important to use more than one instrument to diagnose reading comprehension difficulties, due to the complexity involved. Furthermore, knowledge of the characteristics of each reading comprehension test is essential to the choice of test. The educational implications of children being wrongly diagnosed are discussed.